The Roots of Violence in Western Social Theories: In Search of Solution for Islam and Modernity - Usep Abdul Matin (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2019)
I argue that if we recognize the roots of violence in modern social theories, we may have at least a picture of how to solve the problem of violence for both Islam and modernity. I use the term “violence” to refer to an idea or an action that explicitly endorses revolt or physical conflict in attaining a goal. I will review fourteen social theories of the colonial and post-colonial period from the beginning to the end of the Twentieth Century, as presented by Charles Lemert in his book, Social Theory: The Multicultural & Classic Readings (1993). I refer my understanding of violence and its solutions for Islam and modernity on my interpretation of the types of abuse that I took from Lemert’s book. I discuss my argument in the following subtitles. The first subtitle is an introduction to capitalism as the answer to Islam and modernity. The second item is my finding of the notion of violence as a concept that is originated in the Western social theories of the colonial period. The third point is the degree to which I find that the roots of violence are also originated in the Western social methods of the post-colonial period. The fourth point of my article conveys the term “violence” used in linguistics by two French philosophers: Jacques Derrida and Michelle Foucault. The fifth element concludes this article by strengthening the above-mentioned assumption.